Le théâtre algérien : de la scène traditionnelle à l’interactivité – La pièce « Juha Digital » de Kenza Moubaraki comme modèle. - zine, hafida (El Omda in Linguistics and Discourse Analysis, 2023)
Digitization has dominated the human life domains. So, we’re obliged to live in a digital world. The electronic media have become necessary to all of our needs. Literature isn’t isolated from these changes. Therefore, the digital literature has emerged with its new features and genres including the digital theatre. The interactive play has emerged,with the use of modern techniques consisting in various digital media, in producing or forming the theatrical discourse. It’s a new pattern of literary writing surpassing the traditional comprehension of the act of literary creativity, which focuses on the one creator. It’s presented by several authors. The receptor may also be invited to contribute to. It’s a good example of productive groupwork surpassing the individuality limits to the collective prospects. This study focuses on the Algerian theatre and digitization.Could the Algerian theatre undertake the experience of theatre and digitization? Could it invest this technology in its favour? Could Kanza Mebarki eventually enter the digital interactive theatre?